Challenges of resilience training for military personnel in the Lithuanian Armed Forces - Dalia Prakapienė; Rolanda Kazlauskaitė Markelienė (Problems and Perspectives in Management, 2024)
Resilience is a complex phenomenon that results from the natural human response to adapt to change through the ability to cope with or respond to threats. In today’s security challenges, military personnel are responsible for the defense of their country, and exposure to unfamiliar situations can harm the ability of military personnel to perform successfully. Therefore, this study aims to identify the challenges in resilience training for the Lithuanian Armed Forces military personnel. The study uses a qualitative research method and an in-depth interview. Eight military psychologists participated in the study. The selection criteria for the informants were currently employed/serving in the military with at least five years of experience and participating in resilience training. The results revealed that there has been significant recent attention to and need for resilience training in the Lithuanian Armed Forces, but that resilience development is fragmented. The findings show that the lack of a unified concept of resilience in the Lithuanian Armed Forces complicates the development of a unified resilience training system. Summarizing the organizational aspects of resilience training for military personnel in the Lithuanian Armed Forces, the following key challenges were identified. There is a lack of leadership support for resilience education; the need for the development of trainers or responsible persons involved in resilience education; the lack of a clear perception of the value of resilience education among trainers; the need for unification and systematization of the education system through the updating/creation of the use of a system for feedback and evaluation. AcknowledgmentWe acknowledge General Jonas Žemaitis Military Academy of Lithuania for financial support in publishing this article.